Globality Without Mobility: Ephemera, 1830s–1860s. - Nenzi, Laura (Journal of World History, 2024)
The article "Globality Without Mobility: Ephemera, 1830s–1860s" from the Journal of World History explores the history of globalization in the nineteenth century through the lens of ephemera, focusing on single-page prints that circulated in Tokugawa Japan. These prints, known as imitation rankings, captured disasters, calamities, and societal changes in a concise and visually appealing manner. The article highlights how these ephemera, despite being locally produced and consumed, reflect global trends in the circulation of information and the transformation of print culture. The study sheds light on the interconnectedness of global publishers facing similar challenges and devising innovative tactics to navigate a rapidly changing world.